Auditing practices in local governments : an international comparison - Ferry, Laurence; Ruggiero, Pasquale (Emerald studies in public service accounting and accountability., 2022)
Through a comparative analysis of the development of auditing practices in governments across the globe, Auditing Practices in Local Governments: An International Comparisonprovides a contemporary overview of public sector auditing practices at both local and state level.